2018
DOI: 10.1155/2018/6425857
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Short-Duration Hyperbaric Oxygen Therapy to Improve HbA1c, Leukocyte, and Serum Creatinine in Patients with Diabetic Foot Ulcer Wagner 3-4

Abstract: Objective To evaluate the short-duration hyperbaric oxygen therapy (HBOT) can improve HbA1c levels, leukocyte count, and serum creatinine levels in patients with diabetic foot ulcer (DFU) Wagner 3-4. Methods Blood samples from all DFU patients at Sanglah General Hospital, Denpasar, were taken for HbA1c, leukocyte, and serum creatinine test before debridement procedure, and the patients were then grouped into either standard therapy or standard therapy with HBOT for 10 sessions (combination therapy). At the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…Grimberg-Peters et al [ 40 ], among other groups, showed a supportive effect of HBO in an analysis of the effect of such a treatment aimed at reducing inflammation on the activity of neutrophils isolated from severely injured patients (days 1–2 after trauma). In turn, a statistically significant decrease in the number of leukocytes after therapy combined with HBO compared with baseline was observed by Irawan et al [ 41 ] in patients with a diabetic foot ulcer.…”
Section: Discussionmentioning
confidence: 78%
“…Grimberg-Peters et al [ 40 ], among other groups, showed a supportive effect of HBO in an analysis of the effect of such a treatment aimed at reducing inflammation on the activity of neutrophils isolated from severely injured patients (days 1–2 after trauma). In turn, a statistically significant decrease in the number of leukocytes after therapy combined with HBO compared with baseline was observed by Irawan et al [ 41 ] in patients with a diabetic foot ulcer.…”
Section: Discussionmentioning
confidence: 78%
“…101 Also, HBOT decreases the level of inflammatory markers such as cytokines (interleukin 1 and tumor necrosis factor a), 113,105 C-reactive protein, 101,117 free fatty acid (FFA), and NO 101,102 in the blood of patients with DM. In addition, HBOT improves glucose metabolism in patients with DM and vascular complications, most probably by increasing insulin sensitivity [118][119][120] via upregulation of peroxisome proliferator-activated receptor gamma (PPAR-g) expression 121,122 as well as increase in adiponectin level, which further regulates the expression of glucose transporter 4 by Akt and mediate glucose uptake. 123 Hyperbaric oxygen therapy exerts a beneficial effect on glucose metabolism by reducing hypoxia and inflammation, known for the ability to synergistically inhibit the activity of molecules involved in the insulin signaling cascade.…”
Section: Risk Factors For the Development Of Vascular Complications Imentioning
confidence: 99%
“…An ulcer occurs because, at tissue damage or death, that associated with the degree of peripheral vascular disease in inferior limb and may be accompanied by infection [4], [5]. It is estimated 15-25% of DM patients will develop DFUs with high morbidity, 40-80% will have high infection risk, and 10-20% will require amputation [6].…”
Section: Introductionmentioning
confidence: 99%
“…The standard therapies of DFUs are to regulate normal blood sugar levels, antibiotics medication to prevent and treat infection, ulcer debridement, wound care, off-loading the affected limb, and to improve blood flow or revascularisation [2], [6], [7], [8], [9]. In addition to these standard therapies, there are many adjuvant therapies, such as hyperbaric oxygen therapy (HBOT), growth factor therapy, stem cells therapy [7], [10], autolytic debridement [4], and percutaneous transluminal angioplasty [11].…”
Section: Introductionmentioning
confidence: 99%